Jawność postępowania cywilnego, ze szczególnym uwzględnieniem elektronicznego postępowania upominawczego - Misztal-Konecka, Joanna (Kwartalnik Prawa Publicznego, 2012)
Openness of civil proceedings is a part of the right to access to court protected by Polish Constitution and Article 6 of the European Convention on Human Rights. It is guaranteed also in electronic proceedings by writ of payment (EPU). EPU is a new type of separate procedure introduced into the polish Civil Procedure Code in 2009. EPU may be used to enforce payment of a clearly defined amount, the amount of which is not in dispute as evidence by relevant documentation, such as a bill of acceptance signed by the debtor, demand for payment or invoice. In EPU the access for a plaintiff in realised by using communication system which allows to read records of the proceedings at any time, in any place. A defendant has a choice: can use communication system or read records of the proceedings in any district court.